Centralization and transport of critically ill pediatric patients - Kamidani, Ryo; Okada, Hideshi (Frontiers in Pediatrics, 2025)
BackgroundCaring for critically ill pediatric patients requires specialized expertise, centralized facilities, and efficient transport systems. The centralization of pediatric intensive care units in tertiary centers has enhanced clinical outcomes, resource efficiency, and standardized care. In this study, we provided an updated review of the increase in need for specialized pediatric transport teams.MethodsWe searched PubMed for peer-reviewed literature on the treatment and transport of critically ill pediatric patients, as well as websites of government agencies involved in reporting population prospects. The following search terms were used: pediatric intensive care units, specialized pediatric transport teams, centralization, and helicopter emergency medical services. Thereafter, an inductive qualitative content analysis was performed.ResultsHigh-volume pediatric intensive care units are associated with lower risk-adjusted mortality rates and more efficient resource utilization. However, over-centralization may reduce quality. Effective patient transport depends on skilled personnel, coordination, and stabilization, regardless of the team's composition. Therefore, transport methods should be selected based on a patient's condition, distance, and regional resources. Although helicopters enable rapid transport, they pose risks such as patient-related adverse events, operational hazards, and high costs. Additionally, recent studies questioned the “golden hour” concept, emphasizing stabilization and timely care over speed. Telemedicine plays a crucial role in reducing unnecessary transfers, optimizing resources, and improving access to specialized care.ConclusionsAs aging populations and declining birth rates reshape healthcare needs, the demand for specialized pediatric transport and telemedicine increases. Future strategies must address regional disparities, enhance cost-effectiveness, and integrate advanced technologies such as artificial intelligence to ensure equitable and high-quality pediatric care.